The particularities of the autobiographic novel in the manuscript of Camus’ The first man - Geske, Samara Fernanda A. O. de Lócio e Silva (Manuscrítica: Revista de Crítica Genética, 2014)
This article starts on a personal note in order to explain Catherine Viollet’s role in my research, both for her reflections on the genesis and autobiography as for her guidance during the research in France. My goal is to introduce a discussion on the particularities of the autobiographical novel from the point of view of its creative process and from the analysis of Albert Camus’ manuscript, The first man. Starting from a reflection about the enunciation and the use of proper names, I try to explain the ambivalent space occupied by the autobiographical novel. This particular point of view directs us to a broader reflection on the reasons and implications of using the novel to the writing of the self.